2006
DOI: 10.1097/01.mlr.0000228002.43688.c2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Potentially Avoidable Hospital Readmission Rate as a Routine Indicator of the Quality of Hospital Care

Abstract: Background:The hospital readmission rate has been proposed as an important outcome indicator computable from routine statistics. However, most commonly used measures raise conceptual issues. Objectives: We sought to evaluate the usefulness of the computerized algorithm for identifying avoidable readmissions on the basis of minimum bias, criterion validity, and measurement precision. Research Design and Subjects: A total of 131,809 hospitalizations of patients discharged alive from 49 hospitals were used to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
168
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(179 citation statements)
references
References 40 publications
3
168
2
Order By: Relevance
“…The composite neonatal adverse outcome indicator is a reliable population measure of severe neonatal morbidity utilizing routinely collected data that can easily be applied by other users of population health databases which is an important feature of an indicator (34). The NAOI, along with the maternal morbidity outcome indicator (18), can also be used to monitor the quality of obstetric and neonatal care in a uniform and cost-effective way.…”
Section: Resultsmentioning
confidence: 99%
“…The composite neonatal adverse outcome indicator is a reliable population measure of severe neonatal morbidity utilizing routinely collected data that can easily be applied by other users of population health databases which is an important feature of an indicator (34). The NAOI, along with the maternal morbidity outcome indicator (18), can also be used to monitor the quality of obstetric and neonatal care in a uniform and cost-effective way.…”
Section: Resultsmentioning
confidence: 99%
“…5 It has been reported that a lower quality of inpatient care increases the risk for unplanned early readmission in patients with heart failure, diabetes, or obstructive lung disease, 6 and a recent study concluded that adjusted rates of potentially avoidable readmissions are scientifically sound enough to warrant their inclusion in hospital quality surveillance. 7 On the other hand, another detailed analysis argued that it is difficult to conclude if early readmission is a valid and useful quality indicator. 8 However, overall there is support for readmission rates being used as a surrogate for quality of care delivered in hospitals.…”
mentioning
confidence: 99%
“…1 Unplanned readmissions have often been considered a marker for poor quality inpatient care or ineffective hospital-to-home transitions. [2][3][4][5][6][7] Various interventions using pharmacists and advance-practice nurses have been shown to assist patients with the transition process and reduce readmissions. [7][8][9][10] A patient centered medical home provides a natural foundation on which to support the transition of patients from hospital to outpatient care.…”
mentioning
confidence: 99%